Faktor-faktor yang Mempengaruhi Perilaku Masyarakat terhadap Pencegahan Covid 19 Di Puskesmas Kuranji Kota Padang - Erni Musmiler; Rika Syafitri; Hilmi Yuri Putri; Daeng Ramadhan Salim (Jurnal Amanah Kesehatan, 2022)
Covid 19 data in Kuranji District was recorded as many as 7,286 cases. Based on the observations of researchers in the field, the high number of Covid cases in Kuranji District was due to the indifference of the local community regarding Covid-19, such as not wearing masks, gathering with neighbors, not getting used to washing hands. The purpose of this study is to determine the factors that influence people's behavior towards the prevention of Covid 19 at the Kuranji Public Health Center, Padang City.This research is a quantitative research with descriptive analytic type with a cross sectional study design at the Kuranji Public Health Center, Padang City. Research and data collection was carried out from January to September 2022. The population in this study was 8,287 people and a sample of 99 respondents, the sampling technique was purposive sampling. The data obtained were analyzed univariately and bivariately with frequency distribution and chi-square statistical test.The univariate results showed that the level of knowledge (61.6%) was good, people's attitudes (52.2%) were positive, family support (82.2%) was high, access to information (80.8%) was accessed, community behavior (68.7%) was high. ) tall. The results of the bivariate study based on statistical tests showed that there was a significant relationship between the level of knowledge (p value 0.000), attitudes (p value 0.006), family support (p value 0.000), access to information (p value 0.005) and the behavior of preventing Covid-19 19 at the Kuranji Health Center in the city of Padang.It can be concluded that high knowledge, positive attitude, high family support, seeking information and good behavior are needed in order to prevent the occurrence of Covid 19. It is recommended that the public is expected to be more active in seeking information about the correct Covid-19 prevention so that they can increase knowledge and improve preventive behavior in order to break the chain of transmission of Covid-19